Determinants of Public Perception on Biotechnological Innovations - K. L. Prasanna Kumar; B. Sujatha; G. Pakki Reddy; S. V. Subba Reddy (Journal of Agricultural Extension Management, 2013)
Biotechnology is one of the key technologies which would resolve present burning problems like climate change. Pollution, malnutrition, drought and salinity and lead to sustainable development. Biotechnology has become a complex technology with its wide scope for generating multiple innovations across various industries. Unfortunately there are some apprehensions about biotechnological innovations like r-DNA technology, cloning technology etc. Due to lack of reliable information on biotechnological innovations and their utility in various industries, people are unable to perceive the merits and demerits of biotechnology. Hence it is necessary to address these issues for sustainable scientific governance. In India, the rate of generation and dissemination of inventions in biotechnology is fagging due to societal agitation on use of Bt. technology in food crops like brinjal, maize etc. and ethical concerns over GM animals. This study focuses on determinants of public perception and attitude towards biotechnological innovations